Pain nursing for gynecologic cancer patients - Wu, Wei; He, Xiaodan; Li, Shenjie; Jin, Ming; Ni, Yali (Frontiers in Oncology, 2023)
Gynecological malignancy remains a prevalent cause of mortality among women. Chronic cancer pain, as a severe complication of malignancy and its therapies, accounts for a substantial burden of physical and psychological distress in affected patients. Accordingly, early identification, assessment, and standardized management of such pain are crucial in the prevention or delay of its progression. In the present review, we provide a comprehensive overview of the pathological factors that contribute to pain in patients with gynecological malignancy while highlighting the underlying mechanisms of pain in this population. In addition, we summarize several treatment modalities targeting pain management in gynecologic cancer patients, including surgery, radiotherapy, and chemotherapy. These interventions are crucial for tumor elimination and patient survival. Chronic cancer pain exerts a significant impact on wellbeing and quality of life for patients with gynecologic cancer. Therefore, our review emphasizes the importance of addressing this pain and its psychological sequelae and advocates for a multidisciplinary approach that encompasses nursing and psychological support. In summary, this review offers valuable insights into the pathological factors underlying pain, reviews pain management modalities, and stresses the critical role of early intervention and comprehensive care in enhancing the quality of life of these patients.